Human Resource Management Strategy and Performance Outcomes: A Study of Service Sector Institutions in Nepal - Pradhan, Gopal Man; Pokharel, Puskar Prasad (Journal of Nepalese Management Academia, 2024)
This research work is concentrated to depict the relation and impact of HRM strategies and high-performance outcomes of service sector institutions in Nepal. HRM strategies represent through differentiation strategy, cost reduction strategy and quality focus strategy whereas high performance outcomes represent through productivity, quality and innovation. Employees of two hospitals, one airline, three insurance companies, and four commercial banks are included as samples for analysis in this study. A total of 476 questionnaires were distributed, and 424 (89%) of those copies were fully completed and returned for use in the study. The correlation results suggested that there is positive association between HRM strategies and performance outcomes but cost reduction strategy has high level of correlation with that of performance outcomes. Similarly, while analyzing the beta coefficient, variable of cost reduction strategy sensitivity to performance outcome is high followed by differentiation strategy and quality focus strategy therefore all the variables have positive impact on performance outcomes of service institutions. The research found that all three variables HRM strategies consisting of differentiation strategy, cost reduction strategy and quality focus strategy have positive correlation and impact on performance outcomes of service sector institutions.